Interlayer Raman modes in twisted bilayer transition metal dichalcogenides - Schneider, Eileen; Watanabe, Kenji; Taniguchi, Takashi; Maultzsch, Janina (Physical Review B, 2024)
Twisted bilayer (2L) two-dimensional transition metal dichalgocenides (TMDCs) exhibit a range of novel phenomena such as the formation of moiré excitons and strongly correlated phases. The coupling between the layers is crucial for the resulting physical properties and depends not just on the twist angle but also on the details of the fabrication process. Here, we present an approach for the analysis of this interlayer coupling via Raman spectroscopy. By exciting the C-exciton resonance of the TMDCs, optical (high-frequency) interlayer Raman modes are activated that are too weak in intensity at excitation energies far below the C exciton. This is due to the wave function of the C exciton, which expands - in contrast to A and B excitons - over both layers and therefore couples the layers electronically. We present optical interlayer Raman modes in twisted 2L TMDCs and show that they can be used as a measure of the interlayer coupling between the individual layers.
CRIS-Team Scopus Importer:2024-10-25

Production of Ultrathin and High-Quality Nanosheet Networks via Layer-by-Layer Assembly at Liquid-Liquid Interfaces - Neilson, Joseph; Caffrey, Eoin; Cassidy, Oran; Gabbett, Cian; Synnatschke, Kevin; Schneider, Eileen; Munuera, Jose Maria; Carey, Tian; Rimmer, Max; Sofer, Zdeněk; Maultzsch, Janina; Haigh, Sarah J.; et al. (ACS nano, 2024)
Solution-processable 2D materials are promising candidates for a range of printed electronics applications. Yet maximizing their potential requires solution-phase processing of nanosheets into high-quality networks with carrier mobility (μNet) as close as possible to that of individual nanosheets (μNS). In practice, the presence of internanosheet junctions generally limits electronic conduction, such that the ratio of junction resistance (RJ) to nanosheet resistance (RNS), determines the network mobility via μNS/μNet ≈ RJ/RNS + 1. Hence, achieving RJ/RNS < 1 is a crucial step for implementation of 2D materials in printed electronics applications. In this work, we utilize an advanced liquid-interface deposition process to maximize nanosheet alignment and network uniformity, thus reducing RJ. We demonstrate the approach using graphene and MoS2 as model materials, achieving low RJ/RNS values of 0.5 and 0.2, respectively. The resultant graphene networks show a high conductivity of σNet = 5 × 104 S/m while our semiconducting MoS2 networks demonstrate record mobility of μNet = 30 cm2/(V s), both at extremely low network thickness (tNet < 10 nm). Finally, we show that the deposition process is compatible with nonlayered quasi-2D materials such as silver nanosheets (AgNS), achieving network conductivity close to bulk silver for networks <100 nm-thick.
CRIS-Team Scopus Importer:2025-02-04
Keywords: charge transport; device; nanoplatelets; printed electronics; self-assembly; transistor